Scientific Literasi Pada Pembelajaran IPA Tema Ekosistem di Kelas V SD Inpres Melinani: Indonesia - Berasa, Elfin Enjeli; Pelamonia, Johanes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the level of student literacy in learning Natural Science (IPA) with the theme Ecosystem in Class V of SD Inpres Melinani. The research method used in this study was descriptive quantitative, while the subjects used in the study were 5th grade students consisting of 10 people. The instrument in this study used a questionnaire that had gone through the validity test and then analyzed using descriptive statistical analysis techniques. The results showed that the science literacy of 5th grade students of SD Inpres Melinani in learning science with the theme of ecosystems was at a good level. The average score of students' science literacy is 76.5, which shows that most students have been able to understand the basic concepts of ecosystems, including interactions between living things, ecosystem cycles, and the impact of human activities on the environment.